Reconstructing Cultural Tourism Destinations and Communication Strategies for the Development of a National-Level Cultural Tourism Area in Gegesik, Cirebon Regency, West Java Province - Nurul Chamidah; Nurhidayah Nurhidayah; Yusa Inderapermana; Dwi Kusumayanti (Journal of Social and Policy Issues, 2025)
The development of culture-based tourism has emerged as a key strategy for enhancing the competitiveness of regional destinations, including Cirebon Regency. Gegesik was chosen as the research site due to its rich artistic and cultural heritage, yet it faces challenges such as the absence of representative tourism amenities and limited human resources in tourism management. This study aims to formulate a revitalization concept for the Gegesik town square as a cultural attraction center and to design a communication strategy for developing culture-based tourism at the national level. Using an exploratory qualitative approach, data were collected through documentation, field observations, in-depth interviews with community leaders and local officials, and focus group discussions with academics, artists, and agencies. Analysis employed a communication science perspective to examine interaction patterns, community participation, and message delivery. Findings reveal the square serves as a hub for cultural, artistic, religious, and social activities, with 74 intangible cultural heritage forms, 80 local culinary types, and active art studios. However, its physical condition requires revitalization based on local wisdom. The ACADA model (Assessment, Communication Analysis, Design, Action) guided the formulation of educational tourism programs such as school cultural visits. The study emphasizes combining physical revitalization with participatory communication to strengthen Gegesik’s image as a cultural tourism destination, with recommendations for consistent government support, community capacity building, and sustainable educational initiatives.